High flow nasal cannula for patients undergoing bronchoscopy and gastrointestinal endoscopy: A systematic review and meta-analysis - Tao, Yuan; Sun, Mingyang; Miao, Mengrong; Han, Yaqian; Yang, Yitian; Cong, Xuhui; Zhang, Jiaqiang (Frontiers in Surgery, 2022)
Background: High flow nasal cannula is gaining increasingly used in patients undergoing endoscopic procedures. We undertook this systematic review and meta-analysis to determine whether high flow nasal cannula (HFNC) could effectively minimize the risk of hypoxemia as compared with conventional oxygen therapy (COT). Methods: We performed a comprehensive search of Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and Web of Science. Studies involving the application of HFNC during endoscopic procedures were identified. Results: We included 15 randomized controlled trials (7 bronchoscopy, 8 gastrointestinal endoscopy). Patients receiving HFNC during endoscopic procedures had a significantly lower risk of hypoxemia (defined as SpO2 < 90%) versus COT group (risk ratio = 0.32; 95%CI (0.22 to 0.47), 13 studies, 4093 patients, moderate-quality evidence, I2 = 48.82%, P < 0.001). The lowest SpO2 was significantly higher in HFNC group (mean difference = 4.41; 95%CI (2.95 to 5.86), 9 studies, 1449 patients, moderate-quality evidence, I2 = 81.17%, P < 0.001) than those receiving COT. No significant difference was detected between groups in end-procedure partial pressure of CO2 (standard mean difference = -0.18; 95%CI (- 0.52 to 0.15), 5 studies, 238 patients, moderate-quality evidence, I2 = 42.25%, P = 0.29). Patients receiving HFNC were associated a lower need for airway intervention (risk ratio = 0.45; 95%CI (0.24 to 0.84), 8 studies, 2872 patients, moderate-quality evidence, I2 = 85.97%, P = 0.01) and less procedure interruption (risk ratio = 0.36; 95%CI (0.26 to 0.51), 6 studies, 1562 patients, moderate-quality evidence, I2 = 0.00%, P < 0.001). The overall intubation rate after endoscopy was 0.20% in both group, with no difference detected (risk ratio = 1.00; 95%CI (0.30 to 3.35), 7 studies, 2943 patients, low-quality evidence, I2 = 0.00%, P = 1.00). Conclusion: This systematic review and meta-analysis found moderate to low evidence that the application of HFNC was associated with improved oxygenation, decreased need for airway intervention, and reduced procedure interruption in patients undergoing endoscopic procedures. Future larger sample and high-quality studies are warranted to confirm our result and further investigate the effectiveness of HFNC in patients at risk.